Implementasi enterprise resource planning odoo dalam optimalisasi proses bisnis PT XYZ - Laila Nur Auliani (Qualitative Research of Business and Social Sciences, 2023)
Enterprise Resource Planning (ERP) is an integral system that helps companies integrate and manage various aspects of their operations. PT XYZ To improve operational efficiency and customer service, PT XYZ decided to adopt the Odoo Sales Module, open and integrated ERP software. This research uses a qualitative method with a case study approach. PT XYZ Interviews with mentors from PT Ctech ERP Indonesia and internal data analysis of PT XYZ The analysis results show that the implementation of the Odoo Sales Module has the potential to increase the efficiency of the sales process, saving time and resources. Visibility and control over customer data increases, enabling companies to provide better customer service. Automation of sales tasks and integration between departments can improve operational coordination. Even though PT XYZ has strengths, such as a broad product portfolio and a strong customer base, several weaknesses and challenges still need to be overcome. Growth opportunities can be seen in the e-commerce market, which continues to grow. The threat of intense competition, regulatory changes, and data security risks remain relevant.